تأثیر الاعتماد على تحسین الأداء فى مکتبات کلیات جامعة القاهرة : مکتبة کلیة التخطیط الاقلیمى والعمرانى نموذجا - د. تغرید مصطفى جمعة (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aims at clarifying the impact of the College of Regional andUrban Planning on the academic accreditation in improving the performance of itslibrary through a comparison of the library's status before the college obtains theacademic accreditation and after obtaining the accreditation by comparing thelibrary standard, The same criterion after being prepared by the researcher in theapplied study. And then draw some of the results and indicators and proposesome recommendations that would raise the level of performance in the library.The study has shown improvement in some standards and a rebound in someothers and certain criteria have been proven. The end result is an improvement inthe level of performance of the library after its academic accreditation